The impact of virtual tourism on improving the perception of the image of Algerian tourist destinations from the perspective of the Algerian tourist: a field study on a sample of Algerian tourists - MAAZI, Ghozlane; BAOUT, Lazhar (Journal of Human Sciences, 2025)
This research paper aims to highlight the impact of using virtual tourism on improving the perception of the image of Algerian tourist destinations from the perspective of Algerian tourists. The descriptive approach was used to define the nature of virtual tourism and the image of tourist destinations. The analytical approach was used based on a field study of a purposive sample of Algerian tourists. The study sample consisted of 124 valid individuals for analysis using the SPSS statistical package. The study found that there is a statistically significant effect at a significance level of 5% for virtual tourism on improving the perception of the image of tourist destinations in Algeria from the perspective of the Algerian tourist.